Maria Edgeworth and Abolition Critiquing Character - Runia, Robin (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This Palgrave Pivot offers new readings of Maria Edgeworth's representations of slavery. It shows how Edgeworth employed satiric technique and intertextual allusion to represent discourses of slavery and abolition as a litmus test of character - one that she invites readers to use on themselves. Over the course of her career, Edgeworth repeatedly indicted hypocritical and hyperbolic misappropriation of the sentimental rhetoric that dominated the slavery debate. This book offers new readings of canonical Edgeworth texts as well as of largely neglected works, including: Whim for Whim, "The Good Aunt", Belinda, "The Grateful Negro", "The Two Guardians", and Harry and Lucy Continued. It also offers an unprecedented deep-dive into an important Romantic Era woman writer's engagement with discourses of slavery and abolition. Robin Runia is Associate Professor of English at Xavier University of Louisiana, USA. She has published numerous articles and chapters exploring gender and race in the literature of the long eighteenth century. .
1 Introduction: Edgeworth and Abolition -- 2 Upstaging Abolition: Enlightened Hypocrisy in Whim for Whim -- 3 "The Appearance of Virtue"-Reading Abolition in Belinda -- 4 "The Good Aunt": An Education in Abolition -- 5 Parodic Intervention in "The Grateful Negro" -- 6 Conclusion: Erasing Abolition in "The Two Guardians" and Harry and Lucy Concluded.
Keywords: Literature, Modern-19th century; Literary form; European literature; Comparative literature; Race; Nineteenth-Century Literature; Literary Genre; European Literature; Comparative Literature; Race and Ethnicity Studies